Body, gender, race and fatness in social studies. Gap and future - Alwulaii, Ahmed Nasser (Frontiers in Sociology, 2025)
Sociologists have increasingly turned to the body as a critical aspect of both individual identity and social organization. Some scholars, such as, examine the body's actions within social relations, while others, such as, have demonstrated the power of discourse in controlling and shaping bodies. Additionally, other scholars, like, view the body as a form of physical capital and argue that bodies reflect social class through three major interrelated factors: social location, taste, and habitus. However, sociological studies on the body lack certain dimensions that need to be addressed. In the next section, I will briefly illustrate some of the key gaps in sociological studies of the body concerning gender, race, and fatness. These gaps include an overemphasis on women's bodies, a predominant focus on the white race, a concentration on Western societies while neglecting other parts of the world, and a failure to consider fatness as a social issue. Furthermore, I will briefly discuss future perspectives on sociological studies regarding the intersections of body, gender, and fatness.